ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEPUASAN PASIEN RUJUK ONLINE PADA PASIEN RAWAT JALAN BPJS DI RUMAH SAKIT ADVENT MEDAN TAHUN 2018 - Elmina Tampubolon; Selamat Ginting; Sri Sudewi Pratiwi Sitio (Jurnal Kajian Kesehatan Masyarakat, 2020)
The weakness of referral system has an impact on the use of human resources and in effficent advanced technology, have consequence in accumulation of patients in the hospital and finally impacted to the quality of health service. The purpose of research was to find out the factor of online referral that related to patient satisfaction in agency of social health service outpatients. The research was done using the quantitaive method with the cross sectional approach which analytical survey. The 96 samples is from purposive sampling method. The data instrument used questionnaire with the item correlation 0,361 and cronbach alpha 0,6. The data analysis was done with chi-square test (X 2 test) on the bivariate test, and regression logistic on the multivariate test with α= 0,05. The result of the analysis was related certainty of time (p=0,005), certainty of referral (p= 0,007),waiting time (p=0,034), acces to health service (p=0,011),quality of health service (p= 0,001), health care procces (p=0,004), health care system (p= 0,003) with the patient satisfaction in agency of social health service outpatients and the most dominant variable related with patient satisfaction is certainty of referral (RP=8,886). The research was concluded that there is related the certainty of time, certainty of referral, waiting time, acces to health service, quality of health service, health care procces and health care system related with the patients satisfaction. Suggested to doctor have to be on time in service so that service is more optimal.